From desistance narratives to narratives of rehabilitation: Risk-talk in groupwork for addressing sexual offending - Mullins, Eve (Criminology & criminal justice, 2024)
Risk has become a dominant focus in criminal justice practice. While this can improve the effectiveness of practices for reducing offending, it can also stigmatise and create barriers for those attempting to desist from crime. To explore this apparent dilemma, we applied conversation analysis and discursive psychology to examine risk-talk in 12 video-recorded sessions of a groupwork programme for addressing sexual offending. We found both practitioners and clients oriented to notions of risk in their talk. They drew on risk-talk as a resource to construct narratives that support desistance, emphasising awareness of risks, having control, and gaining hope and agency over the future. However, risk-talk was resisted when it challenged the client’s self-presentation. Building on previous empirical and theoretical work on desistance and criminal justice practice, we found it is possible for people to incorporate aspects of risk into their personal narratives in order to weave a narrative of rehabilitation.